Neutrality Principles of WTO Dispute Settlement Mechanism: Legal and Moral Dimensions (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the neutrality principle of the WTO dispute settlement system, which functions as a quasi-judicial body in the settlement of international trade disputes. Given the system’s resemblance to traditional courts, its effectiveness in ensuring justice hinges on its adherence to neutrality, ensuring fairness, impartiality, and the rule of law. Recent developments, such as the United States obstruction of the Appellate Body, underscore the tension between maintaining neutrality and addressing external pressures that may compromise this foundational principle. This study analyzes the complexities of the neutrality dynamic in the WTO dispute settlement mechanism and argues for the organization’s imperative to protect neutrality amidst emerging challenges. the method used in this study is juridical normative with historical-descriptive characteristics. The research method used is qualitative. The findings of this paper will highlight the need to protect the neutrality principle of the WTO dispute settlement mechanism and the need for change or clarification of the confusion that this blending of economic or political power in DSM, and not beyond that the neutrality of WTO is the heart of this research.